DSS Query Optimization and Effect of Input Output / Communication Cost Metrics - Sharma, M; Singh, G; Singh, R (International Journal of Computer Sciences and Engineering, 2025)
Decision Support System (DSS) query is an important type of distributed query. It plays an imperious role in decision making practise. However, it ingest loads of Input Output (I/O), processing and communication assets. Here, a 3-Join DSS query has been optimized using entropy and restricted chromosome based DSS query optimizer (ERC_QO). A study is carried out to inspect the consequences of varying the ratio of I/O and communication costs over Total Costs (total system resources). It is perceived that by plummeting the I/O to communication costs ratio, the communication costs can be more commendably optimized. For a 3-Join DSS query, the communication costs have been reduced by 90% approximately. Moreover, the Total Costs of 3-Join DSS query is abridged by 2%.